32‐1: RGBW OLED Microdisplays for Wearable Augmented Reality. Issue 1 (28th June 2021) - Sun, Yan; Zhu, Zhijian; Peng, Xiangjun; Shi, Tiankuo; Lu, Pengcheng; Zhang, Xiaomang; Sun, Wei; Chen, Xiaochuan; Dong, Xue; Wang, Hui
Abstract : In order to meet the demand of high luminance and low power consumption for wearable AR (Augmented Reality) applications, two types of 0.71‐inch RGBW OLED micro‐displays were developed, reaching luminance of more than 5000 cd/m2 with resolution of FHD (1920 × 1080). RGBW mapping and sub‐pixel rendering algorithms were proposed to achieve good performance.